Expression and properties of wild-type and mutant forms of the Drosophila sex comb on midleg (SCM) repressor protein. - Bornemann, D.; Miller, E.; Simon, J. (Genetics, 1998)
The Sex comb on midleg (Scm) gene encodes a transcriptional repressor of the Polycomb group (PcG). Here we show that SCM protein is nuclear and that its expression is widespread during fly development. SCM protein contains a C-terminal domain, termed the SPM domain, which mediates protein-protein interactions. The biochemical function of another domain consisting of two 100-amino-acid-long repeats, termed "mbt" repeats, is unknown. We have determined the molecular lesions of nine Scm mutant alleles, which identify functional requirements for specific domains. The Scm alleles were tested for genetic interactions with mutations in other PcG genes. Intriguingly, three hypomorphic Scm mutations, which map within an mbt repeat, interact with PcG mutations more strongly than do Scm null alleles. The strongest interactions produce partial synthetic lethality that affects doubly heterozygous females more severely than males. We show that mbt repeat alleles produce stable SCM proteins that associate with normal sites in polytene chromosomes. We also analyzed progeny from Scm mutant germline clones to compare the effects of an mbt repeat mutation during embryonic vs. pupal development. We suggest that the mbt repeat alleles produce altered SCM proteins that incorporate into and impair function of PcG protein complexes.